Gmür's (2d from the right) visit to the "Asociacion de Empleados de Correos y Telegrafos del Uruguay". Text on the back
Gmür's (2d from the right) visit to the "Asociacion de Empleados de Correos y Telegrafos del Uruguay". Text on the back.